Relationship between parenting practices and behavioral problems of children attending a Tertiary Mental Health Institute of North East India - Amina Ahmed; A Baruah; L B Siddeswara (Indian Journal of Psychiatric Nursing)
Introduction: The parent plays a vital role in promoting and supporting the overall development of children from infancy to adulthood. Parenting practices are related to different outcomes in children's life. Hence, the researcher aimed to assess the relationship between parenting practices and behavioral problems of children. Subjects and Methods: A quantitative approach and correlational design was used. Total 80 primary caregivers of children (6–17 years), attending a Tertiary Mental Health Institute of North East India were selected using systematic random sampling technique. Data were collected using Sociodemographic Pro forma, Alabama Parenting Questionnaire, Strength and Difficulties Questionnaire after obtaining written informed consent from the participants. Results: Overall 55% of the participants had scored toward more positive parenting practices and 56.2% toward less negative parenting practices. Regarding behavioral problems of children, 77.5% had total difficulty levels in the abnormal range with 52.5% at substantial risk for emotional symptoms, 78.8% for conduct problems, 43.8% for hyperactivity/inattention, and 73.8% for peer problems. Participant's negative parenting practices were positively correlated with total difficulty score as well as with conduct problems, hyperactivity, and peer problems. Finding further showed that participant's positive parenting practices had a significant association with their educational status, occupation, family income, place of residence, children's birth order, use of mobile phone by children, and negative parenting practices had a significant association with their history of substance use, fights between parent, and children's last academic performance. These findings can be incorporated for developing intervention module for parents of children in the hospital setting as well as in the community.